2021
DOI: 10.2147/copd.s338074
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Programmes Within Three Days of Hospitalization for Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis

Abstract: Objective To evaluate the efficacy and safety of early pulmonary rehabilitation (PR) (ie, <3 days of hospitalization) in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods Embase, Web of Science, PubMed and Cochrane Library were searched from their inception to 1 April 2021. Randomized controlled trials were included if they observed the efficacy of early PR in AECOPD patients. Study selection, data extraction, risk of bias and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…The use of NMES may be effective in preventing muscle atrophy and weakness, particularly in patients with declining activity levels. A review of PR that included a variety of programs did not conclude that limb muscle strength improved (Zhang et al., 2021). Therefore, NMES is considered more useful for maintaining and improving limb muscle strength; however, the installation of NMES, which requires devices, requires an examination of cost and demand.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NMES may be effective in preventing muscle atrophy and weakness, particularly in patients with declining activity levels. A review of PR that included a variety of programs did not conclude that limb muscle strength improved (Zhang et al., 2021). Therefore, NMES is considered more useful for maintaining and improving limb muscle strength; however, the installation of NMES, which requires devices, requires an examination of cost and demand.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al conducted a meta-analysis of 14 randomized controlled trials on early RPs in patients with COPD exacerbations [ 19 ]. Most patients were in their 60s, and only three studies included participants older than 70 years in both groups; therefore, the participants in our study were considered relatively old.…”
Section: Discussionmentioning
confidence: 99%
“…As a comprehensive intervention measure, PR shows beneficial advantages for relieving clinical symptoms, increasing exercise endurance, and improving quality of life. 36 PR is considered the first-line nondrug therapy for chronic respiratory diseases and proven effective in childhood asthma. [37][38][39] Exercise training, the cornerstone of PR, comes in a variety of forms, and it is yet unclear which may It has been reported that exercise can improve cardiorespiratory fitness and muscle strength, to relieve or control asthma.…”
Section: Discussionmentioning
confidence: 99%
“…As a comprehensive intervention measure, PR shows beneficial advantages for relieving clinical symptoms, increasing exercise endurance, and improving quality of life 36 . PR is considered the first‐line nondrug therapy for chronic respiratory diseases and proven effective in childhood asthma 37–39 .…”
Section: Discussionmentioning
confidence: 99%